(untitled) (Encuentros, 2020)
The article addresses the training of graduates in computer education from the current post-pandemic conditions. At first, an analysis is made of current solutions regarding the training of university professionals and the impossibility of assuming them from the social and historical context. In a second moment, the current conditions of Cuban higher education in general and in particular of the degree are described. Later the methods used are described and finally the results obtained. Keywords: teacher training, computer science education, computer science teacher training, pandemic training.